Peningkatan Pengelolaan UKM di Era Digitalisasi pada Nisa Bakery di Kelurahan Surodinawan Kecamatan Prajurit Kulon Kota Mojokerto - Titiek Rachmawati; Nekky Rahmiyati (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
In the Era of Digitalization, SMEs must keep up with developments. The problems faced by SMEs Nisa Bakery include the production process not being optimal because there is no mixer with the required capacity, a lack of understanding regarding the production space, where the production space is still one with a storage area for both raw materials and auxiliary materials, which is also integrated with packaging of finished goods (bread), financial recording is still simple, there is no separation between recording household and business finances, while marketing still depends on orders. The aim of this community service is to help solve the problems that occur at Nisa Bakery. The method used to solve the problem is providing equipment grants in the form of a mixer with a capacity of 10 liters, training on the use and maintenance of the mixer, expanding marketing using online media, business management assistance which includes training and mentoring on business management, finance/accounting. The results of this community service were the provision of a standing mixer machine with a capacity of 10 liters, understanding of inventory control methods, technical training in simple bookkeeping and marketing digitalization training.